Development of the anterior lateral line system through local tissue‐tissue interactions in the zebrafish head. Issue 12 (11th August 2020) - Iwasaki, Miki; Yokoi, Hayato; Suzuki, Tohru; Kawakami, Koichi; Wada, Hironori
Abstract: Background: The distribution of sensory organs is important for detecting environmental signals efficiently. The mechanosensory receptors of the lateral line system, neuromasts, are stereotypically distributed over the head and body surface of fish, although how neuromasts arise in these predetermined positions during development remains unclear. Results: We investigated the development of the anterior lateral line (ALL) system in zebrafish head. The ALL neuromasts formed in the predetermined positions through proliferation and differentiation of (a) nonmigratory lateral line primordia, (b) migratory primordia, (c) interneuromast cells connecting preexisting neuromasts, and (d) budding primordia. We demonstrated that R‐spondin2 (Rspo2), an activator of Wnt/β‐catenin signaling, is required for the development of a particular set of neuromasts associated with hyomandibular cartilage. Further genetic analyses suggested that Rspo2, which emanates from the hyoid mesenchyme, acts on the adjacent neuromast progenitor cells to stimulate their proliferation through activating Wnt/β‐catenin signaling. Conclusion: This study has revealed novel mechanisms for neuromast positioning through local tissue‐tissue interactions, providing insights into the development and evolution of the vertebrate head. Key Findings: Development of the anterior lateral line system in the zebrafish head is described. Rspo2 is required for the development of a particular set of neuromasts associated with hyomandibular cartilage. Rspo2, which emanates from the head mesenchyme, acts on adjacent neuromast progenitor cells to stimulate their proliferation. Novel mechanisms for neuromast positioning provide insights into the development and evolution of the vertebrate head.